Preparation of Lignosulfonate-Based Carbon Foams by Pyrolysis and Their Use in the Microencapsulation of a Phase Change Material - Palazzolo, Martín Alejandro (2018)
Currently, further research on the valorization of lignin is needed to shift biorefineries from a conceptual basis to profitable practice. Providing global warming is a major concern as well, the use of lignin as the sole precursor to elaborate materials with thermal energy storage (TES) applications is especially welcomed in the search for new sustainable solutions. To this end, the preparation of on-demand macroporous carbon foams from calcium lignosulfonate (CaLS) by pyrolysis is described herein, and their capability to microencapsulate phase change materials (PCMs) dedicated to the passive refrigeration of buildings by TES is further assessed as a proof of concept. The as-produced CaLS-based foams were found to be efficient containers for this purpose, displaying any appreciable leakage of PCMs. Furthermore, the thermal properties of the final materials were satisfactory as well, showing that the support does not affect the PCM performance negatively. Considering the process to produce such materials is not only straightforward but also relies on an inexpensive, widely available carbon precursor, it is expected that it serves as a starting point for pilot studies in TES projects.